Review on neuroimaging in pediatric-type diffuse low-grade gliomas - Chen, Jing; Qi, Xin; Zhang, Mengjie; Zhang, Jing; Han, Tong; Wang, Chunxiang; Cai, Chunquan (Frontiers in Pediatrics, 2023)
The fifth edition of the World Health Organization Classification of Tumors of the Central Nervous System (WHO CNS5) has identified a new classification system for tumors of the brain and spinal cord, highlighting the pivotal role of molecular diagnosis in accurately categorizing neoplasms. In addition to previous classifications, one of the key distinctions lies in categorizing pediatric-type diffuse low-grade gliomas (pDLGGs) and pediatric-type diffuse high-grade gliomas (pDHGGs) as distinct tumor types. Although similar in histology and morphology, pediatric diffuse gliomas are completely different from the adult type with respect to the molecular genetic characteristics, prognosis, and treatment strategies. pDLGG includes four tumor types, namely, diffuse astrocytoma, MYB- or MYBL1-altered; angiocentric glioma; polymorphous low-grade neuroepithelial tumor of the young (PLNTY); and diffuse low-grade glioma, MAPK pathway-altered, three types of which are newly recognized tumor types. Herein, we review the clinical characteristics, histopathological and molecular genetic characteristics, neuroimaging features, and prognosis of pDLGG and summarize the neuroimaging key points in diagnosing different tumor types. This review aims to evaluate and update the relevant pDLGG features and advances in neuroimaging that may assist in differential diagnosis, surgery planning, and prognostic determination of these tumor types and provide accurate diagnostic information for clinical colleagues.